BIOCHEMICAL COMPOSITION AND BIOLOGICAL POTENTIAL OF ORA-PRO-NOBIS FRUIT: AN OVERVIEW - Leirson Rodrigues da Silva; Ana Rosa de Figueiredo; Milena Maria Tomaz de Oliveira; Cristiane Maria Ascari Morgado; Pedro Augusto Resende Rimoli; Lilia Aparecida Salgado de Morais (Revista de Agricultura Neotropical, 2023)
Exotic fruit crops, such as ora-pro-nobis, play an important role in human nutrition, making them an excellent base for low-calorie diets. Recent research has shown that ora-pro-nobis fruit is rich in many nutritional and bioactive compounds, making it highly valued for its unique taste, aroma, and color. As the popularity of this fruit grows in economic markets, it is important to have a comprehensive reference for its nutritional and bioactive benefits. This review provides a valuable source for current knowledge about nutritional and bioactive compositions, as well as the relationship of its biologically active components with beneficial and functional effects on human health, through scientifically proven information. By harnessing the rich properties of ora-pro-nobis fruit, we can pave the way for further development of functional foods, as well as its applications in the nutraceutical, cosmetic, and pharmaceutical industries.